Teaching and Engaging International Students: People-to-People Empathy and People-to-People Connections - Tran, Ly Thi (Journal of International Students, 2020)
International student mobility has been increasingly subject to turbulences in politics, culture, economics, natural disasters, and public health. The new decade has witnessed an unprecedented disruption to international student flows and welfare as a consequence of the COVID-19 outbreak. COVID-19 has laid bare how fragile the current transactional higher education model is, in Australia and in other major destination countries like the United States, United Kingdom, Canada and New Zealand. This health crisis hitting international education presents a range of challenges for host universities. In such a fallout, the connection between university communities and international students is more critical than ever. This connection is vital not only to university’s operations and recovery but more importantly, to international students’ learning and wellbeing. This in turn will have longer term impacts on host countries’ and universities’ sustainable international recruitment and reputation as a study destination. Therefore, it is timely to reflect on how we view and conceptualize the way we engage and work with international students. This article presents a new frame for conceptualizing the teaching, learning, and engagement for international students, which emphasizes people-to-people empathy and people-to-people connections.Conceptualize Student Connection Through Formal and Informal CurriculumDis/connection has been argued to play “an important role in shaping international students’ wellbeing, performance and life trajectories” (Tran & Gomes, 2017, p. 1). Therefore, it is important to frame international student connectedness not only within the context of formal teaching and learning on campus, but also in a broader setting, taking into account the dynamic, diverse, and fluid features of transnational mobility.Some of the primary dimensions of international student connection vital to their academic and social experience and wellbeing have been identified as:• Connection with the content and process of teaching and learning• Bonding between host teachers and international students• Engagement with the university communities• Interaction between domestic and international students and among international peers• Integration into relevant social and professional networks, the host community, and the host society• Connection with family and home communities• Online and digital connectionBased on interviews with around 400 international students, teachers, and international student support staff across different research projects, I identified four main principles underpinning effective engagement and support for international students. Most participants stressed the importance of understanding international students’ study purposes, needs, expectations, and characteristics in the first place in order to meaningfully and productively engage with and cater for this cohort (Tran, 2013). Second, effective teaching of and engagement with international students is based on understanding not only their academic needs but also other aspects that are interlinked with their academic performance, including pastoral care needs, mental health, employment, accommodation, finance, life plans, and aspirations. Third, a sense of belonging to the content of teaching and learning and the pedagogy used by teachers is essential to international students’ engagement with the classroom community. In this regard, connection is intimately linked to international students being included and valued intellectually and culturally in teaching and learning, and in being treated as partners (Green, 2019; Tran, 2013) rather than ‘others’ in the curriculum. Fourth, to position international students as truly an integral component of campus communities, it is essential to develop explicit approaches to engage them not only academically and interculturally, but also mentally and emotionally, especially during hard-hitting crises in international education such as the 2019–2020 COVID-19 outbreak, the 2003 SARS epidemic, and the 2001 September 11 attacks.Productive ConnectednessThe lack of engagement between international and domestic students is often identified as a primary area for improvement for universities that host international students, especially in Anglophone countries (Leask, 2009). While international education is supposed to strengthen people-to-people connections and enrich human interactions, ironically it is this lack of connection with the local community, including local students, that international students feel most dissatisfied about in their international education experience. To support and optimize the learning and wellbeing of international students, productive connectedness is essential. Productive connectedness is not simply providing the mere conditions for interaction between domestic and international peers (Tran & Pham, 2016). These conditions alone cannot ensure meaningful and real connectedness but can just lead to artificial or surface engagement between international students and the host communities. Productive connectedness is centered around creating real opportunities for international and local students to not only increase their mutual understandings, but importantly also to reciprocally learn from the encounter of differences and share, negotiate, and contribute to building knowledge, cultural experiences, and skills on a more equal basis. In this regard, productive connectedness is integral to optimizing teaching and learning for international students.Teaching and Learning for International StudentsOver the past 15 years, I and my colleagues have undertaken various research on conceptualizing the teaching and learning process for international students, an evolving and dynamic field of scholarship (Tran, 2011; Tran, 2013a, 2013b; Tran & Nguyen, 2015; Tran & Gomes, 2017; Tran & Pham, 2016). Figure 1 summarizes the six interrelated dimensions of teaching and learning for international students emerging from our research: connecting, accommodating, reciprocating, integrating, “relationalizing,” and empathy.ConnectingIt is critical in effective teaching and learning for international students that conditions are provided to engage them intellectually, culturally, socially, and affectively. Curriculum, pedagogies, and assessment activities should aim at supporting international students to make transnational knowledge, skills, experience, and culture, as well as people-to-people connections (Tran, 2013).AccommodatingEffective teaching and learning for international students cannot be achieved without an effort to understand their purposes to undertake international education, their cultural and educational backgrounds, their characteristics, their identities, and their aspirations. Good teaching and learning practices in international education are often built on educators’ capacities to tailor their curriculum and pedagogies to cater to international students based on an understanding of their study purposes, backgrounds, and identities.ReciprocatingReciprocal learning and teaching is integral to international education (Tran, 2011). It is centered around positioning international students as co-constructors of knowledge and educators as reciprocal co-learners (Tran, 2013b). It refers to extending beyond mutual understanding and respect for diversity, to validate and reciprocally learn from diverse resources, experiences, and encounters of differences that international classrooms can offer. This is vital to making international students feel included and valued as an integral part of the curriculum and the university community.IntegratingIntegrating refers to the purposeful incorporation of international examples, case studies, materials, and perspectives into the curriculum. Strategies to diversify the teaching and learning content and pedagogies are closely connected with de- Westernizing the curriculum and moving away from Euro-centric content (Tran, 2013a). Integrating contributes to enriching students’ global awareness, world mindfulness, and intercultural competence, which are central to internationalizing student experience and outcomes.“Relationalizing”“Relationalizing” is crucial in assisting domestic and international students to develop open-minded and ethno-relative perspectives. Engaging students in a comparing–contrasting and reflexive process about professional practices, prior experiences, and cultural norms in different countries represents a critical step in assisting them to develop multiple frames of reference and build capacities to relationally learn from richly varied perspectives and experiences that an international classroom can offer.EmpathyInternational students’ sense of belonging to the classroom and university community significantly depends on the empathy local teachers and students display toward them. Teachers can develop activities that enable students to develop an understanding and empathy toward what it feels like to be an international student in an unfamiliar academic and social environment, studying in a language that is not their mother tongue. One of the teacher-participants in our research shared an activity she used to help all students develop empathy:I asked for volunteers, I’d speak to them in English and they had to answer in their language. The group had to try and figure out from their body language and tone of voice what they were actually saying to me...But what I try and make them understand that part of the reason we’re doing that, not in English, is because it’s like excluding the local students and it’s making them look like foreigners and to understand the challenge.ConclusionEffective practices in engaging, teaching, and learning for international students enrich the international classroom community and optimize learning for all, including international and domestic students and teachers themselves (Carroll & Ryan, 2007; Tran, 2013b; Tran & Le, 2018). Good pedagogical practices in teaching and learning for international students depend on teachers’ commitment to step outside of their comfort zone and take on a new learning curve (Tran, 2013). It is, however, vital that internationalizing teaching and learning and building intercultural interactions among students from diverse backgrounds and—in particular between international and domestic students—should be prioritized at both program and course development levels, making them explicit in course objectives and assessments (Tran & Pham, 2016). It is crucial to have a coherent whole-institution approach toward a purposeful, transformative, and empathetic internationalization of teaching and learning content, pedagogies, and assessment, one that is supported by the broader institution’s core goals about internationalizing the student experience and graduate outcomes. An internationalized program of learning for international and domestic students alike should prioritize enhancing their abilities to learn from global encounters, abilities to connect and empathize, skills to navigate intercultural relationships, and skills to capitalize on opportunities and also to deal with pressures and challenges. Importantly, the teaching and learning for international students needs to be built on an approach emphasizing people-to-people empathy and people-to-people connections.